Determinants of Bank Profit Growth: A Study of PT. Bank NTB Syariah in 2019-2023 - Sahirul Alim; Hendri Saleh; Windra Sopiana (Future Techno-Science, 2025)
The growth of company profits, including PT. Bank NTB Syariah is determined by many factors. Return On Asset, (ROA), Return On Equity (ROE) and Debt to Equity Ratio (DER) are predictor factors for the profits generated. This study aims to analyze the factors, namely Return On Asset, Return On Equity, Debt to Equity Ratio, both partially and simultaneously, on profit growth. The statistical test used is Multiple Linear Regression. The population in the study is the financial statements of PT Bank NTB Syariah in 2019-2023, totaling 60 financial statements. The results of the study indicate that partially Return On Asset has an effect on profit growth, the calculated t value is > from the t table value or 2.382 > 2.00324 or sig (0.032 < 0.05). Furthermore, Return On Equity has an effect on profit growth, this is evidenced by the calculated t value > from the t table value or 2.365 > 2.00324 or sig (0.029 < 0.05). While Debt to Equity Ratio does not affect profit growth with the calculated t value < from the t table value or 0.702 < 2.00324 or sig (0.486 > 0.05). The conclusion of this study is that simultaneously Return On Asset, Return On Equity, Debt to Equity Ratio have an effect on profit growth. Simultaneous test with three predictors, namely ROA, ROE and DER on Profit Growth shows that the value of F-calculation (3.496) > Ftable (2.77) and sig value 0.015 < 0.05 means that simultaneously Return On Asset (ROA),